Possibilities of the environment of the modern school in the prevention of risk behavior in adolescents - Moskvina, Elena Vladimirovna (Razvitie obrazovaniâ (Online), 2023)
The purpose of the article was to consider the possibilities of a modern school in the prevention of risky behavior of adolescents. The focus of the research seems relevant due to the fact that the scientific solution meets the urgent needs of the practice of organizing these activities and fills a certain gap in modern research in overcoming risky behaviors of the younger generation. Methods of comparative analysis of psychological and pedagogical scientific sources were used in the preparation of the material, theoretical analysis of monographic and dissertation materials, documentation on the problems of research using generalization, comparison, systematization and modeling was carried out. The article considers a possible field of prevention of risky behavior at school, which lies at the intersection of three components of the environment of an educational organization. These include motivational-value (formation of factors that stimulate subjects of prevention to obtain a predictable positive result), social-subjective (formation of factors that contribute to the formation and development of subjectivity of adolescents in academic, extracurricular, extracurricular work, additional education, self-government, amateur activity), actualization – creative (formation of factors of creative realization of a teenager, aimed at on the formation of the ability to constructive risk) components. As a result, the author came to the conclusion that it is possible to achieve the predicted result of prevention of risky behavior of adolescents using the capabilities of a modern school resulting from the creation and replenishment of its components.